2022
DOI: 10.3233/jad-215602
|View full text |Cite
|
Sign up to set email alerts
|

An Alternatively Spliced TREM2 Isoform Lacking the Ligand Binding Domain is Expressed in Human Brain

Abstract: Background: Genetic variants in TREM2 are strongly associated with Alzheimer’s disease (AD) risk but alternative splicing in TREM2 transcripts has not been comprehensively described. Objective: Recognizing that alternative splice variants can result in reduced gene expression and/or altered function, we sought to fully characterize splice variation in TREM2. Methods: Human blood and anterior cingulate autopsy tissue from 61 donors were used for end-point and quantitative PCR and western blotting to identify an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…As a new variant of TREM2 lacking exon 2 has recently been described in different areas of the human brain but not yet in the entorhinal cortex [ 45 , 46 , 47 ], we were interested to know if this isoform ( D2-TREM2 ) is also expressed in the entorhinal cortex. Thus, we confirmed its expression in the entorhinal cortex and observed that it was upregulated in AD samples (FC = 2.02, p -value < 0.05), being the second transcript of TREM2 most expressed; however, after adjusting for age and gender, the difference between AD samples and controls was no longer statistically significant (FC = 1.28, p -value = 0.50) ( Figure 3 B,C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a new variant of TREM2 lacking exon 2 has recently been described in different areas of the human brain but not yet in the entorhinal cortex [ 45 , 46 , 47 ], we were interested to know if this isoform ( D2-TREM2 ) is also expressed in the entorhinal cortex. Thus, we confirmed its expression in the entorhinal cortex and observed that it was upregulated in AD samples (FC = 2.02, p -value < 0.05), being the second transcript of TREM2 most expressed; however, after adjusting for age and gender, the difference between AD samples and controls was no longer statistically significant (FC = 1.28, p -value = 0.50) ( Figure 3 B,C).…”
Section: Resultsmentioning
confidence: 99%
“…Sequences of primer pairs were designed using the Real-Time PCR tool (IDT, Coralville, IA, USA) and Primer3 software and D2-TREM2 primers described in Shaw B.C. et al [ 47 ] were included ( Supplementary Materials Table S1 ). The relative expression level of mRNA in a particular sample was calculated as previously described [ 80 ], and the geometric mean of GAPDH and ACTB genes was used as a reference to normalize expression values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA and cDNA samples used for this study have been extensively described previously [ 22 , 23 , 24 , 25 ]. Briefly, RNA and genomic DNA were purified from anterior cingulate samples provided by the University of Kentucky AD Center, and the RNA was converted to cDNA as described [ 22 , 23 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA and cDNA samples used for this study have been extensively described previously [ 22 , 23 , 24 , 25 ]. Briefly, RNA and genomic DNA were purified from anterior cingulate samples provided by the University of Kentucky AD Center, and the RNA was converted to cDNA as described [ 22 , 23 , 25 ]. Samples were divided into two groups based on AD neuropathology, as quantified by the National Institute on Aging–Reagan Institute (NIARI) criteria, which include both neuritic plaques and neurofibrillary tangles [ 26 ].…”
Section: Methodsmentioning
confidence: 99%